(ii) Planning revision hip arthroplasty. Issue 2 (April 2015) - Tofighi, Medhi; Jones, Stephen A.
Abstract: Pre-operative planning is an integral part of revision hip arthroplasty which has advanced significantly over the past two decades. It has progressed from a crude procedure with limited armamentarium to a sophisticated operation with a predictably better outcome. In general, revision procedures have an increased frequency of complications and a poorer outcome for the patient in comparison with primary hip replacement. Therefore detailed planning prior to intervention is a fundamental aspect of revision hip surgery, to both minimize adverse events and hopefully maximize patient outcome. Each patient can present with their own unique problems and the planning process involves consideration of the patient as a whole and then specifically the failed hip replacement itself. A structured approach to revision hip surgery in general and specifically to the individual patient will best prepare the surgeon, thus leading to reduced patient morbidity and mortality.